Modernizing Smallholder Agriculture and Achieving Food Security: An Exploration in Machinery Services and Labor Reallocation in China - Baoling Zou; Ashok K. Mishra (Institute of Labor Economics (IZA), 2024)
Worldwide, most farms are small and family-operated. This study discusses the future of smallholder agriculture in China, where most farms are small, and farms' parcels are fragmented. The study puts forward a framework of vertical division of labor and specialized production in agriculture. We posit that hiring machinery services could be a pathway to connect smallholders with modern agriculture and achieve food security in China. Using household-level data from China, this study examines the impact of hiring machinery services on farm productivity, food security, and rural households' welfare. Findings show that mechanization services increased rural Chinese families' food security and agricultural productivity. Hiring machinery services improves smallholders' income by influencing the input efficiency of maize production. At the same time, increased mechanization implied greater participation in off-farm work. In other words, more family labor and time are allocated to off-farm work, which results in higher total income and increased consumption expenditures. Our findings highlight the importance of technology to improve smallholder agriculture and food security, not only in China but also in other South and Southeast Asian countries.
Keywords: Q12; C36; J22; 330; production efficiency; machinery services; household welfare; food security